2022
DOI: 10.3389/fimmu.2022.972503
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 inhibitors plus anti-angiogenic therapy with or without intensity-modulated radiotherapy for advanced hepatocellular carcinoma: A propensity score matching study

Abstract: BackgroundWhether intensity-modulated radiotherapy (IMRT) can enhance the efficacy of the programmed death (PD)-1 inhibitors combined with anti-angiogenic therapy for hepatocellular carcinoma (HCC) is unclear. Therefore, we conducted this multicenter retrospective study to investigate the efficacy of the combination of PD-1 inhibitors with anti-angiogenic therapy and IMRT.MethodsFrom April 2019 to March 2022, a total of 197 patients with HCC [combination of PD-1 inhibitors with anti-angiogenic therapy and IMRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“… 4 , 5 , 31 Furthermore, our previous research discovered that programmed death 1 (PD-1) inhibitors combined with anti-angiogenic therapy and intensity-modulated radiotherapy can extend the OS of advanced HCC patients to 20.1 months. 32 Moreover, selective internal radiotherapy (SIRT) extended the OS of advanced HCC patients to 8.8 months. 33 Zhang et al found that the mOS of inoperable HCC patients receiving TACE-lenvatinib was 30.5 months.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 31 Furthermore, our previous research discovered that programmed death 1 (PD-1) inhibitors combined with anti-angiogenic therapy and intensity-modulated radiotherapy can extend the OS of advanced HCC patients to 20.1 months. 32 Moreover, selective internal radiotherapy (SIRT) extended the OS of advanced HCC patients to 8.8 months. 33 Zhang et al found that the mOS of inoperable HCC patients receiving TACE-lenvatinib was 30.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy can greatly activate the autoimmunity of HCC patients but the therapeutic performance in clinical trials remain unsatisfactory till now ( Chen et al, 2022 ). For example, the objective response rate of HCC was still low in the patient received combination therapy of PD-1/PD-L1 inhibitors and targeted drugs ( Su et al, 2022b ). In this work, we analyzed the tumor microenvironment and found that the prognosis-related gene DAPK1 was correlated with several immune cells, immunostimulators and targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
“…After eliminating duplicates (n = 257), titles and abstracts were browsed and filtered. The full text of the remaining 42 studies was screened, and 10 articles [13][14][15][16][17][18][19][20][21][22] were finally included according to the inclusion criteria. The literature review and identification processes are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine included studies [13,[15][16][17][18][19][20][21][22] reported ORR and DCR as clinical outcomes. The pooled ORR after PD1/ PDL1 inhibitors combined with RT and anti-angiogenic agents (RIT) was 59% (95% CI: 48-70%, P = .00), whereas the pooled DCR was 92% (95% CI: 81-103%, P = .00) (Figs.…”
Section: Tumor Responsementioning
confidence: 99%
See 1 more Smart Citation